2022
DOI: 10.3389/fcimb.2022.1042735
|View full text |Cite
|
Sign up to set email alerts
|

Dual-fluorescent reporter for live-cell imaging of the ER during DENV infection

Abstract: Infection by flaviviruses leads to dramatic remodeling of the endoplasmic reticulum (ER). Viral replication occurs within virus-induced vesicular invaginations in the ER membrane. A hallmark of flavivirus infection is expansion of the ER membrane which can be observed at specific time points post infection. However, this process has not been effectively visualized in living cells throughout the course of infection at the single cell resolution. In this study, we developed a plasmid-based reporter system to mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous research has shown that influenza A virus, foot and mouth disease viruses, Senecavirus A, West Nile virus and dengue virus have been engineered to carry a reporter gene for high throughput monoclonal antibody and antiviral assays [ 25 , 26 , 27 , 28 , 29 , 30 ]. Tagged EV-A71 and CV-A16 of the Enterovirus A are constructed by the same strategy to insert the GFP, nano luciferase, or gaussia luciferase gene between the 5′-UTR and the N-terminus of VP4, with the addition of a 2A protease cleavage site (ITTLG) at C-terminus of the 5′-UTR [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that influenza A virus, foot and mouth disease viruses, Senecavirus A, West Nile virus and dengue virus have been engineered to carry a reporter gene for high throughput monoclonal antibody and antiviral assays [ 25 , 26 , 27 , 28 , 29 , 30 ]. Tagged EV-A71 and CV-A16 of the Enterovirus A are constructed by the same strategy to insert the GFP, nano luciferase, or gaussia luciferase gene between the 5′-UTR and the N-terminus of VP4, with the addition of a 2A protease cleavage site (ITTLG) at C-terminus of the 5′-UTR [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%